Method and system for analyzing mechanical property degradation mechanism of limestone in karst area

By conducting dynamic dissolution tests in CO2 solution environment, combined with SEM, CT scanning and multiple fractal theory, the problem that the existing technology cannot accurately fit the deterioration law of rock mechanical properties is solved, and the mechanism of deterioration of mechanical properties of limestone in karst areas is realized In-depth analysis provides scientific basis for engineering design.

CN119437890APending Publication Date: 2025-02-14KUNMING PROSPECTING DESIGN INSTITUTE OF CHINA NONFERROUS METALS INDUSTRY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411650810.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing dry-wet cycle tests cannot accurately fit the mechanical properties of rock mass during dynamic dissolution, and the acidic corrosion media in the actual environment and the chemical solution environment arranged in the test are quite different.

Method used

Dynamic dissolution test under CO2 solution environment was constructed through gas-liquid circulation, and the deterioration rules of uniaxial compressive strength, tensile strength and shear strength parameters of limestone under dynamic dissolution were studied, and SEM, CT scan and multiple fractal theory were used. Perform quantitative analysis.

Benefits of technology

In-depth analysis of the mechanism of deterioration of the mechanical properties of limestone in karst areas is achieved, more accurate data support is provided, and scientific basis for engineering design and safety assessment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119437890A_ABST
    Figure CN119437890A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rock mass analysis, in particular to a karst area limestone mechanical property degradation mechanism analysis method and system, and the method comprises the following steps: obtaining limestone of a karst area to construct a limestone test sample; testing the limestone test sample to obtain a test result; observing the limestone test sample to obtain a microscopic feature observation result of the limestone test sample; analyzing the microscopic characteristic observation result to obtain a microscopic characteristic analysis result of the limestone test sample; and analyzing the limestone mechanical property degradation mechanism by combining the test result and the microscopic characteristic analysis result. The dynamic corrosion test is constructed to more accurately fit the rock mass degradation condition in the natural environment, and the change rule of the limestone mechanical property parameters is researched based on the dynamic corrosion test, so that the mechanical property degradation mechanism of the limestone in the karst area is analyzed, and a reliable theoretical technical support is provided for engineering application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rock mass analysis, in particular to a method and system for analyzing the mechanical property degradation mechanism of limestone in karst areas. Background Art

[0002] Under natural conditions, continuous physical and chemical reactions will occur between the rock mass and the aqueous solution in the karst area. After time accumulation, the dynamic dissolution environment of water-rock interaction will gradually change the microstructure and mineral composition of the rock mass, thereby promoting the expansion of the pores inside the rock mass, affecting the strength and deformation characteristics of the rock mass, and forming potential weak zones. This creates prerequisites for external factors such as rainfall and earthquakes to induce karst collapse, poses major challenges to the geological safety of foundations and slopes, and brings safety hazards to the project.

[0003] Therefore, it is necessary to conduct experimental research on the degradation effect of the mechanical properties of rock mass. At present, many scholars have carried out a series of experimental studies on the problem of dynamic dissolution degradation of limestone rock mass, and carried out dry-wet cycle tests on sandstone, diorite and other rocks to analyze the degradation law of rock mechanical properties under the action of dry-wet cycle. The immersion dissolution stage of the dry-wet cycle test is carried out in a single static closed equilibrium system. In the actual water-rock process of rock mass, the corrosive medium is mostly in a flowing state. The mineral ions in the rock matrix will migrate with the solution medium after precipitation, and will not be enriched on the rock surface to delay the dissolution process of rock minerals. The water-rock dissolution is always in a non-equilibrium state. Therefore, the dry-wet cycle test under a single static closed equilibrium system cannot accurately fit the dynamic dissolution process of rock mass.

[0004] The degradation of the mechanical properties of rock mass is also controlled by the properties of the erosion solution, especially when the erosion solution is rich in acidic substances. In view of the influence of the solution properties, some scholars have carried out dry-wet cycle tests on sandstone in an acidic solution environment, analyzed the changes in its physical parameters and mechanical properties, and provided a certain reference basis for the study of the erosion effect of acidic solutions on rocks. However, the acidic erosion medium in the actual occurrence environment of the rock mass is formed by CO2 dissolved in an aqueous solution, but the immersion solution is directly configured by a chemical solution, and the constructed acidic solution environment is quite different from the actual occurrence environment of the rock mass.

[0005] Therefore, in order to more accurately fit and analyze the degradation process of the rock mass, the present invention constructs a dynamic dissolution test in a CO2 solution environment by means of gas-liquid circulation. A new water-rock-CO2 action test method is proposed, and a dynamic dissolution test is carried out on the rock mass in the slope drawdown zone under dynamic dissolution, and the degradation law of the uniaxial compressive strength, tensile strength and shear strength parameters of the limestone test samples are studied and analyzed. The energy change and crushing fractal change of the limestone test samples are quantitatively analyzed. Based on the SEM electron microscope images, the degradation characteristics of the micromorphology of the limestone test samples with the dynamic dissolution cycle are evaluated and analyzed. At the same time, CT scanning technology and multiple fractal theory are used to quantitatively characterize the damage evolution characteristics of the internal pores of the limestone test samples, and then the degradation mechanism of the mechanical properties of the limestone is analyzed. Summary of the invention

[0006] In view of the defects in the prior art, the present invention provides a method and system for analyzing the degradation mechanism of the mechanical properties of limestone in karst areas.

[0007] In order to achieve the above-mentioned purpose, in the first aspect, the present invention provides a method for analyzing the degradation mechanism of the mechanical properties of limestone in karst areas, the method comprising the following steps: obtaining limestone in karst areas to construct limestone test samples; obtaining test results based on testing the limestone test samples; observing the limestone test samples to obtain microscopic characteristic observation results of the limestone test samples; obtaining microscopic characteristic analysis results of the limestone test samples based on analysis of the microscopic characteristic observation results; and analyzing the degradation mechanism of the mechanical properties of limestone by combining the test results and the microscopic characteristic analysis results. The present invention obtains limestone test samples and conducts dynamic dissolution tests and microscopic characteristic observations, and combines the dynamic dissolution test results with the microscopic characteristic analysis results to deeply analyze the degradation mechanism of the mechanical properties of limestone in karst areas, which is helpful for scientifically evaluating the stability of limestone in karst areas and providing an effective reference basis for geological engineering design and disaster warning in practical engineering applications.

[0008] Optionally, the limestone in the karst area is obtained to construct a limestone test sample, including: obtaining a cylindrical limestone sample by pre-processing the limestone in the karst area; obtaining a limestone characteristic sample based on the cylindrical limestone sample; and obtaining a limestone test sample according to the limestone characteristic sample. The present invention prepares the limestone in the karst area into a standard cylindrical limestone sample, and then obtains the limestone characteristic sample and screens out the limestone test sample, thereby ensuring the consistency and accuracy of subsequent dynamic dissolution tests, providing reliable test materials for analyzing the mechanical properties of limestone, and helping to improve the accuracy and reliability of the analysis.

[0009] Optionally, the test results obtained based on the test on the limestone test sample include: obtaining the stress-strain change relationship of the limestone test sample based on the test; obtaining the energy change relationship of the limestone test sample according to the test; constructing the tensile strength change relationship of the limestone test sample according to the test; and obtaining the shear stress-shear displacement change relationship of the limestone test sample by using the test. The present invention obtains the dynamic dissolution test results by testing the limestone test sample through the dynamic dissolution test, which provides data support for the in-depth analysis of the mechanical properties of limestone, helps to further study and analyze the mechanical property degradation mechanism of limestone, and provides a scientific basis for engineering design and safety assessment.

[0010] Optionally, the energy change relationship of the limestone test sample obtained according to the test includes: in, is the total energy of the limestone test sample, is the stress of the limestone test sample, The present invention quantifies the total energy of the limestone test sample through the stress and strain of the limestone test sample, and provides data support for further analyzing the energy changes inside the limestone test sample.

[0011] Optionally, the observation of the limestone test sample to obtain the microscopic characteristic observation results of the limestone test sample includes: obtaining the microscopic morphological characteristics of the limestone test sample based on the scanning observation of the limestone test sample; obtaining the microstructural characteristics of the limestone test sample based on the scanning observation of the limestone test sample. The present invention accurately obtains the microscopic morphological characteristics and microstructural characteristics of the limestone test sample by scanning and observing the limestone test sample, which provides a basis for in-depth exploration of the mechanical properties of limestone and provides data support for analyzing the relationship between the macroscopic mechanical properties and microscopic characteristics of the limestone test sample.

[0012] Optionally, the microstructure analysis result of the limestone test sample obtained based on the analysis of the microstructure observation result includes: preprocessing the microstructure feature to obtain the microstructure feature image of the limestone test sample; characterizing the microstructure feature based on the microstructure image to obtain the microstructure characterization result of the limestone test sample; and obtaining the microstructure analysis result of the limestone test sample based on the analysis of the microstructure characterization result. The present invention obtains the microstructure analysis result by preprocessing and further characterizing the microstructure feature image of the limestone test sample, which provides data support for in-depth understanding of the changes in the microstructure characteristics of limestone, and provides a scientific basis for further analyzing the intrinsic relationship between the mechanical properties of limestone and microstructure characteristics.

[0013] Optionally, characterizing the microstructure of the limestone test sample based on the microscopic characteristic image to obtain a microstructure characterization result includes: in, Multifractal The partition function of order, is the order of the statistical moment, is the side length of the square box, Count the total number of square boxes, is the traversal count, For the The probability distribution of pixels in a square box is: is the mass scaling function. The present invention is based on constructing a multi-fractal The order partition function constructs an accurate multifractal spectrum through reliable data, which provides strong data support for characterizing the pore structure characteristics of limestone test samples.

[0014] Optionally, the mass scaling function comprises: in, is the mass scaling function, is the side length of the square box, is the multifractal order partition function, The invention provides data support for obtaining the multifractal spectrum of the limestone test sample by constructing a mass scaling function, thereby improving the accuracy and reliability of the evaluation result.

[0015] Optionally, the combination of the test results and the microscopic characteristic analysis results is used to analyze the degradation mechanism of the mechanical properties of limestone, including: constructing the variation relationship between the microstructural degradation characteristics and the uniaxial compressive strength of the limestone test sample based on the microstructural characteristic analysis results; analyzing the degradation mechanism of the mechanical properties of limestone according to the variation relationship between the microstructural degradation characteristics and the uniaxial compressive strength. Based on the microstructural characteristic analysis results, the present invention constructs the relationship between the microstructural degradation characteristics and the uniaxial compressive strength of limestone, deeply analyzes the degradation mechanism of the mechanical properties of limestone, provides a scientific basis for the evaluation of the mechanical properties of limestone, and provides a reference for engineering applications.

[0016] In the second aspect, the present invention provides a system for analyzing the mechanism of mechanical property degradation of limestone in karst areas. The system executes the method for analyzing the mechanism of mechanical property degradation of limestone in karst areas provided by the present invention. The system includes an input device, an output device, a processor and a memory. The gain lies in that the hardware facilities integrated by the present invention have excellent performance, the input device, the output device, the processor and the memory are interconnected, and the information transmission between the various components is smooth. Through the interaction of multiple hardware facilities, an efficient information processing system is constructed. The present invention constructs a dynamic dissolution test to more accurately fit the situation of rock mass degradation in a natural environment, and studies the changes in the mechanical parameters of limestone through dynamic dissolution tests. It can more accurately and effectively analyze the degradation of the mechanical properties of limestone in karst areas, and provide reliable experimental references and theoretical technical support for practical engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A flow chart of a method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas according to an embodiment of the present invention; Figure 2 A schematic diagram of the mineral composition and content of limestone in a karst area according to an embodiment of the present invention; Figure 3 is a stress-strain relationship curve diagram of a limestone test sample according to an embodiment of the present invention; Figure 4 is a graph showing changes in peak stress and elastic modulus of a limestone test sample according to an embodiment of the present invention; Figure 5 Energy-strain relationship graph of limestone test samples of an embodiment of the present invention; Figure 6 A graph showing the change in the crushing fractal dimension and dissipated energy ratio of the limestone test sample according to an embodiment of the present invention; Figure 7 A schematic diagram of changes in tensile strength of limestone test samples according to an embodiment of the present invention; Figure 8 is a shear stress-shear displacement relationship curve diagram of a limestone test sample according to an embodiment of the present invention; Fig. 9 is a shear strength variation curve diagram of a limestone test sample according to an embodiment of the present invention; Fig.10 A schematic diagram of the change in cohesion and internal friction angle of a limestone test sample according to an embodiment of the present invention; Fig.11 A schematic diagram of changes in microscopic morphological characteristics of a limestone test sample according to an embodiment of the present invention; Fig.12 A schematic diagram of changes in microstructure characteristics of a limestone test sample according to an embodiment of the present invention; Fig.13A multi-fractal spectrum of a limestone test sample according to an embodiment of the present invention; Fig.14 It is a curve diagram of the variation of multiple fractal characteristic parameters of the limestone test sample according to the embodiment of the present invention; Fig.15 It is a curve diagram of the multi-fractal characteristic parameters and the stage degradation rate of uniaxial compressive strength of the limestone test sample according to the embodiment of the present invention; Fig.16 This is a framework diagram of a system for analyzing the degradation mechanism of the mechanical properties of limestone in karst areas according to an embodiment of the present invention. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention will be described in detail below. It should be noted that the embodiments described herein are only for illustration and are not intended to limit the present invention. In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is obvious to those of ordinary skill in the art that these specific details do not need to be adopted to implement the present invention. In other examples, in order to avoid confusing the present invention, known circuits, software or methods are not specifically described.

[0019] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "in one embodiment," "in an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. In addition, it should be understood by those of ordinary skill in the art that the figures provided herein are for illustrative purposes and that the figures are not necessarily drawn to scale.

[0020] See also Figure 1 An embodiment of the present invention provides a method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas, the method comprising the following steps: S1. Obtain limestone test samples of limestone structures in karst areas.

[0021] Among them, S1 specifically includes the following steps: S11. Pre-treating the limestone in the karst area to obtain a cylindrical limestone sample.

[0022] Specifically, in this embodiment, representative limestone is obtained from the slope drawdown zone of the reservoir area of ​​the construction project in the karst region.

[0023] For more details, see Figure 2, the figure is a schematic diagram of the mineral composition and content of limestone in the karst area. The X-ray diffraction test of the obtained limestone obtained the mineral composition and content of the limestone as follows: calcite 65.8%, dolomite 34.2%.

[0024] Furthermore, the obtained limestone is subjected to X-ray fluorescence spectroscopy analysis to obtain the main element oxides and contents of the limestone, as shown in Table 1: Table 1 In this embodiment, the limestone obtained from the karst area is processed into a 50mm×100mm cylindrical limestone sample in accordance with the rock testing specifications, and the two ends and sides of the cylindrical limestone sample are polished so that the unevenness at both ends of the cylindrical limestone sample is less than 0.05mm, and the deviation between the end face and the axis is less than 0.25°.

[0025] S12. Obtain a limestone characteristic sample based on the cylindrical limestone sample.

[0026] Specifically, in this embodiment, cylindrical limestone samples with obvious defects are removed by appearance screening, and cylindrical limestone samples with large wave velocity dispersion are removed by longitudinal wave velocity measurement.

[0027] Furthermore, after screening, the remaining cylindrical limestone samples are used as characteristic limestone samples.

[0028] S13. Obtaining a limestone test sample according to the limestone characteristic sample.

[0029] Specifically, in this embodiment, the limestone characteristic sample is placed in a constant temperature and humidity oven for drying, and then taken out and placed indoors to naturally cool to room temperature to obtain a dry limestone characteristic sample.

[0030] The temperature of the constant temperature and humidity oven is set to 105°C, and the drying time is 24 hours.

[0031] Furthermore, the dried limestone characteristic sample is subjected to dynamic dissolution to obtain a limestone test sample.

[0032] Among them, in this embodiment, the duration of a dynamic dissolution cycle is 48 hours, and the dry limestone characteristic sample needs to be subjected to 30 dynamic dissolution cycles. The dynamic dissolution solution is replaced after every 5 dynamic dissolution cycles, and the limestone test samples obtained under 0, 5, 10, 15, 20, 25 and 30 dynamic dissolution cycles are taken as the experimental control group.

[0033] S2. Obtaining test results based on testing the limestone test sample.

[0034] Among them, S2 specifically includes the following steps: S21. Obtaining the stress-strain variation relationship of the limestone test sample based on the test.

[0035] Specifically, in this embodiment, see Figure 3 , the figure shows the stress-strain relationship curve of the limestone test sample. The limestone test samples obtained under different dynamic dissolution cycles are subjected to uniaxial compression tests to construct the stress-strain relationship curve.

[0036] It should be noted that 0n, 5n, 10n, 15n, 20n, 25n and 30n in the figure represent 0, 5, 10, 15, 20, 25 and 30 dynamic dissolution cycles respectively.

[0037] More specifically, according to Figure 3 As shown in the figure, with the increase of dynamic dissolution cycle, the stress-strain curves of the limestone test samples all show a downward shift to varying degrees, the attenuation rate of residual stress gradually decreases, and the stress-strain curves of the limestone test samples gradually change from "single peak" to "multi-peak", and the ductility and plasticity characteristics of the limestone test samples gradually increase.

[0038] For further information, see Figure 4 , the figure shows the peak stress and elastic modulus change curve of the limestone test sample. The limestone test samples obtained from different dynamic dissolution cycles are subjected to uniaxial compression tests to construct the peak stress and elastic modulus change curve of the limestone test samples.

[0039] In this embodiment, according to Figure 4 As shown in the figure, with the increase of dynamic dissolution cycle, the peak stress and elastic modulus of the limestone test sample both show a decreasing trend. After 30 dynamic dissolution cycles, the peak stress of the limestone test sample decreased from 132.31MPa to 29.63MPa, a decrease of 77.60%, and the elastic modulus of the limestone test sample decreased from 83.43GPa to 39.91GPa, a decrease of 52.17%.

[0040] S22. Obtaining the energy change relationship of the limestone test sample according to the test.

[0041] Wherein, S22 specifically includes the following steps: S221. Analyze the energy changes of limestone test samples.

[0042] Specifically, during the uniaxial compression test on the limestone test sample, the essence of the degradation of the mechanical properties of the limestone lies in the storage and dissipation of energy inside the limestone rock mass.

[0043] More specifically, in this embodiment, during the uniaxial compression test, the total energy input to the limestone test sample is used as the total energy of the limestone test sample. As the load continues to increase, the total energy of the limestone test sample undergoes energy conversion, with part of the energy being stored in the limestone test sample in the form of elastic strain energy, and the other part being dissipated due to plastic deformation and damage deformation of the limestone test sample.

[0044] Furthermore, assuming that there is no energy exchange with the outside world during the uniaxial compression test, and ignoring the kinetic energy loss of the limestone test sample during deformation, the energy conversion equation of the energy conversion satisfies the following relationship according to the first law of thermodynamics: in, is the total energy of the limestone test sample, is the elastic strain energy stored in the limestone test sample, For dissipated energy.

[0045] In this embodiment, the total energy input to the limestone test sample during the uniaxial compression test satisfies the following relationship: in, is the total energy of the limestone test sample, is the stress of the limestone test sample, is the strain of the limestone test sample.

[0046] During the uniaxial compression test, according to the elastic deformation theory and Hooke's law, the elastic strain energy stored in the limestone test sample satisfies the following relationship: in, is the elastic strain energy stored in the limestone test sample, is the stress of the limestone test sample, is the elastic modulus of the limestone test sample.

[0047] According to the energy conversion equation, the expression of the total energy and the expression of the elastic strain energy, the dissipated energy of the limestone test sample during the uniaxial compression test satisfies the following relationship: in, is the dissipated energy, is the total energy of the limestone test sample, is the elastic strain energy stored in the limestone test sample, is the stress of the limestone test sample, is the strain of the limestone test sample, is the elastic modulus of the limestone test sample.

[0048] For further information, see Figure 5 , the figure shows the energy-strain relationship curve of the limestone test sample. In this embodiment, the energy change of the limestone test sample under different dynamic dissolution cycles is studied and analyzed by using a uniaxial compression test, and the energy-strain relationship curve of the limestone test sample is established.

[0049] Figure 5 (a) is the total energy-strain relationship curve of the limestone test sample, based on Figure 5 As shown in (a), the growth rate of the total energy of the limestone test sample gradually decreases with the increase of the dynamic dissolution cycle, and the peak value of the total energy increases from 106.05 kJ / m 3 Reduced to 12.40 kJ / m 3 , a decrease of 88.31%.

[0050] Figure 5 (b) is the elastic strain energy-strain relationship curve of the limestone test sample, according to Figure 5 As shown in (b), the growth rate of the elastic strain energy of the limestone test sample gradually decreases with the increase of the dynamic dissolution cycle, and the peak value of the elastic strain energy increases from 80.70 kJ / m 3 Reduced to 8.57 kJ / m 3 , a decrease of 89.38%.

[0051] Among them, the peak value of the elastic strain energy is the energy storage limit of the limestone test sample, which reflects the ability of the limestone test sample to store energy. When the strain is the same, the deformation type of the limestone test sample without dynamic dissolution is mainly the deformation of the solid medium that can store elastic strain energy. After dynamic dissolution, the microcracks inside the limestone test sample gradually develop, the solid medium decreases, and the plastic deformation increases, which leads to a decrease in the energy storage of the limestone test sample and a decrease in the elastic strain energy.

[0052] It should be noted that, in this embodiment, since the uniaxial compression test process adopts load control and the limestone test sample is a brittle material, it is difficult to quantitatively control the stage after the stress peak. Therefore, this embodiment selects the stage before the stress peak to perform energy change analysis on the limestone test sample.

[0053] S222. Analyze the relationship between the crushing fractal dimension and dissipated energy of limestone test samples.

[0054] Specifically, in this embodiment, the debris of the limestone test sample after each uniaxial test is collected, and the debris is passed through multiple layers of sieves in sequence, and the mass of the debris sieved by each sieve is measured.

[0055] Wherein, the apertures of the multi-layer sieves are 60 mm, 40 mm, 20 mm, 5 mm, 2 mm, 1 mm, 0.5 mm and 0.25 mm respectively.

[0056] More specifically, based on the fractal geometry mass-size relationship, the fragment size distribution equation of the limestone test sample satisfies the following relationship: Taking the logarithm of both sides of the fragment size distribution equation yields the following relationship: in, For particles smaller than The accumulated mass of limestone test sample fragments is is the total mass of the fragments of the limestone test sample, is the sieve particle size, is the maximum particle size of the limestone test sample fragments, is the crushing fractal dimension of the limestone test sample.

[0057] Furthermore, in this embodiment, Simplified to , and then in - In the double logarithmic coordinate system, linear fitting is performed on each set of data obtained from the uniaxial compression test, and the slope of the fitting line is , and then the crushing fractal dimension of the limestone test samples under different dynamic dissolution cycles was obtained.

[0058] For further information, see Figure 6 , the figure shows the change curve of the crushing fractal dimension and the dissipated energy ratio of the limestone test sample. The uniaxial compression test is carried out on the limestone test sample to obtain the change curve of the crushing fractal dimension and the dissipated energy ratio of the limestone test sample under different dynamic dissolution cycles.

[0059] In this embodiment, according to Figure 6As shown in the figure, with the increase of dynamic dissolution cycle, the fractal dimension of the limestone test sample gradually decreases, from 2.01 to 1.81, while the proportion of dissipated energy gradually increases, from 23.90% to 30.97%; it shows that the sample without dynamic dissolution can basically not release energy through plastic deformation, as long as the internal tensile crack exceeds the critical size, it will rapidly expand and lead to splitting failure, with obvious brittle failure characteristics and high degree of fragmentation; and with the increase of dissolution cycle, the internal damage of the limestone test sample is aggravated, and more energy absorbed from the outside is converted into dissipated energy, which makes the proportion of dissipated energy gradually increase, the plastic deformation ability of the rock sample is improved, and more plastic deformation is produced under the action of external load, so that the stress can be redistributed, and then the tensile failure will not occur prematurely, which reduces the degree of fragmentation of the limestone test sample and reduces the fractal dimension accordingly.

[0060] S23. Construct a tensile strength variation relationship of the limestone test sample according to the test.

[0061] For details, see Figure 7 , the figure is a schematic diagram of the change in tensile strength of the limestone test sample. Based on the Brazilian splitting test, the tensile strength of the limestone test sample under different dynamic dissolution cycles is analyzed, and then the schematic diagram of the change in tensile strength of the limestone test sample is obtained.

[0062] In this embodiment, according to Figure 7 As shown in the data, with the increase of dynamic dissolution cycle, the tensile strength of the limestone test samples gradually decreases. The tensile strengths of the limestone test samples under 0, 5, 10, 15, 20, 25 and 30 dynamic dissolution cycles are 3.37MPa, 3.17MPa, 2.76MPa, 2.28MPa, 2.05MPa, 1.52MPa and 0.91MPa, respectively. The reduction rates of the tensile strength of the limestone test samples under different dynamic dissolution cycles are 5.93%, 18.10%, 32.34%, 39.17%, 54.90% and 73.00%, respectively.

[0063] S24. Using the test, obtain the shear stress-shear displacement variation relationship of the limestone test sample.

[0064] For details, see Figure 8 , the figure shows a shear stress-shear displacement relationship curve diagram of the limestone test sample. In this embodiment, a direct shear test is performed on the limestone test sample to obtain the shear stress-shear displacement relationship curve diagram of the limestone test sample under four constant normal stresses.

[0065] The four constant normal stresses are 1MPa, 3MPa, 5MPa and 7MPa, respectively. Figure 8 (a) Figure 8 (b) Figure 8 (c) and Figure 8 (d).

[0066] In this embodiment, according to Figure 8 As shown in the figure, under each constant normal stress, with the increase of dynamic dissolution cycle, the shear stress-shear displacement curve of the limestone test sample moves downward as a whole, the shear strength peak of the limestone test sample gradually decreases, and the stress decay rate gradually decreases after reaching the shear strength peak, while the stage change rate of strain increases slowly, indicating that the shear strength degradation effect of the limestone test sample is obvious under the action of dynamic dissolution. At the same time, the brittle failure characteristics of the limestone test sample gradually weaken, and the ductile characteristics gradually enhance.

[0067] For further information, see Fig. 9 , the figure shows a shear strength variation curve of the limestone test sample. In this embodiment, the shear strength peak values ​​of the limestone test samples in different dynamic dissolution cycles are statistically analyzed to draw the shear strength variation curve of the limestone test sample.

[0068] In this embodiment, according to Fig. 9 As shown in the figure, with the increase of dynamic dissolution cycle, the shear strength of limestone test samples gradually decreases, showing an overall deterioration trend of first steep and then slow. The shear strength degradation process of limestone test samples can be roughly divided into the following three stages: In the early stage of dynamic dissolution (0n~10n), the shear strength of the limestone test samples deteriorated slowly and the slope of the curve was small. Under the four constant normal stresses, the stage shear strength degradation value of the limestone test samples only accounted for 2.92%~10.74% of the total degradation value.

[0069] In the middle stage of dynamic dissolution (10n~20n), the shear strength degradation of the limestone test samples is significantly greater than that in the early stage of dynamic dissolution, and the slope of the curve becomes larger. Under the four constant normal stresses, the stage shear strength degradation values ​​of the limestone test samples account for 8.23%~18.25% of the total degradation value.

[0070] In the late stage of dynamic dissolution (20n~30n), the shear strength of the limestone test samples deteriorated rapidly, and the slope of the curve was large. Under the four constant normal stresses, the stage shear strength degradation values ​​of the limestone test samples accounted for 23.32%~35.59% of the total degradation values.

[0071] For further information, see Fig.10, the figure is a schematic diagram of the changes in cohesion and internal friction angle of the limestone test sample. In this embodiment, the Mohr-Coulomb strength criterion is adopted to analyze the changes in cohesion and internal friction angle of the limestone test sample under different dynamic dissolution cycles according to the shear strength peak value and constant normal stress, and then a schematic diagram of the changes in cohesion and internal friction angle of the limestone test sample is constructed.

[0072] in, Fig.10 (a) is a schematic diagram of the cohesion change of the limestone test sample. Fig.10 (b) Schematic diagram of the change of internal friction angle of limestone test sample.

[0073] In this embodiment, according to Fig.10 As shown in the figure, with the increase of dynamic dissolution cycle, the cohesion and internal friction angle of the limestone test samples decreased. The cohesion decreased from 17.02MPa to 8.01MPa, a decrease of 52.95%, and the internal friction angle decreased from 34.27° to 20.04°, a decrease of 41.51%. Moreover, the stage attenuation rate of the cohesion and internal friction angle of the limestone test samples generally showed an increasing trend. The stage degradation rate of cohesion increased from 6.13% to 18.37%, and the stage degradation rate of internal friction angle increased from 3.19% to 9.97%.

[0074] S3. Observe the limestone test sample to obtain microscopic characteristic observation results of the limestone test sample.

[0075] Among them, S3 specifically includes the following steps: S31. Obtaining microscopic morphological characteristics of the limestone test sample based on scanning observation of the limestone test sample.

[0076] For details, see Fig.11 , the figure is a schematic diagram of the changes in the microscopic morphological characteristics of the limestone test samples. In this embodiment, the limestone test samples under different dynamic dissolution cycles are scanned and observed using a SEM scanning electron microscope observation method to obtain a schematic diagram of the changes in the microscopic morphological characteristics of the limestone test samples.

[0077] In this embodiment, Fig.11 The microscopic morphological characteristics of the limestone test samples after 0 dynamic dissolution cycles, 15 dynamic dissolution cycles, and 30 dynamic dissolution cycles are shown respectively; Fig.11As shown in the figure, before dynamic dissolution, the microscopic surface of the limestone test sample is relatively flat, the mineral particles are tightly connected, the particle boundary contours are clearly visible, flat and evenly distributed, the degree of overlapping and stacking is low, the pores are poorly developed, and most of them are scattered; after different degrees of dynamic dissolution, the edges and corners of the apparent mineral particles of the sample are gradually dissolved, the particle size is reduced and varies in size, the pores and cracks between the particles gradually develop and expand, forming larger amorphous dissolution holes and grooves, the number of pores increases accordingly and becomes interconnected, the originally neat and dense mineral particles become loose and broken, and gradually form a porous and loose surface microstructure.

[0078] S32. Obtain microstructural characteristics of the limestone test sample based on scanning observation of the limestone test sample.

[0079] For details, see Fig.12 , the figure is a schematic diagram of the changes in the microstructural characteristics of the limestone test samples. In this embodiment, CT scanning is performed on the limestone test samples with different dynamic dissolution cycles to obtain CT slice images containing the pore distribution characteristics of the limestone test samples, and then a schematic diagram of the changes in the microstructural characteristics of the limestone test samples is constructed.

[0080] In this embodiment, according to Fig.12 As shown in the figure, before dynamic dissolution, the porosity of the limestone test sample was 0.04%, the pore size was mainly distributed in 6-30μm, the pore size accounted for 98.99%, and the maximum pore size was 44.49μm; after 15 dynamic dissolution cycles, the porosity of the limestone test sample was 5.12%, the pore size was mainly distributed in 54-100μm, the pore size accounted for 29.7%, and the maximum pore size was 310.25μm; after 30 dynamic dissolution cycles, the porosity of the limestone test sample reached 17.67%, the pore size was mainly distributed in 300-400μm, the pore size accounted for 34.26%, and the maximum pore size was 384.56μm. With the increase of dynamic dissolution cycles, the proportion of small pores in the limestone test sample gradually decreased, and the proportion of large pores gradually increased.

[0081] S4. Obtaining microscopic characteristic analysis results of the limestone test sample based on the analysis of the microscopic characteristic observation results.

[0082] Wherein, S4 specifically includes the following steps: S41, preprocessing the microstructure characteristics to obtain a microstructure characteristic image of the limestone test sample.

[0083] Specifically, in this embodiment, the CT slice image is binarized to obtain a binary CT slice image, where white represents the pores of the limestone test sample, and the corresponding pixel is 1, and black represents the rock matrix of the limestone test sample, and the corresponding pixel is 0.

[0084] S42. Characterize the microstructural features based on the microscopic feature image to obtain a microstructural characterization result of the limestone test sample.

[0085] Specifically, in this embodiment, the box technique in the multifractal method is used to perform statistical analysis on the limestone test samples.

[0086] In this embodiment, boxes with equal sides are arranged in the binary CT slice image to determine whether the box contains pixels marked as 1. If so, the box is marked as 1, otherwise, it is marked as 0, and the total number of boxes marked as 1 is counted.

[0087] The total number of boxes marked as 1 is counted, and the total number of boxes satisfies the following relationship: in, Count the total number of square boxes, is the side length of the square box, is an index related to multifractal characteristics.

[0088] In this embodiment, by changing the side length of the box, the total number of boxes marked as 1 is repeatedly counted, and the internal structural feature information of the limestone test sample is obtained by combining the number of boxes and the probability distribution of the pixels in the box.

[0089] The probability distribution of the pixels in the box and the probability distribution of the pixels being 1 in the box satisfy the following relationship: in, For the The probability distribution of pixels in the box being 1, For the The number of pixels in a box that are 1, It is the total number of pixels with a pixel value of 1 in the binary CT slice image.

[0090] Further, the multifractal is calculated based on the probability distribution The order partition function satisfies the following relationship: in, Multifractal The partition function of order, is the order of the statistical moment, is the side length of the square box, Count the total number of square boxes, is the traversal count, For the The probability distribution of pixels in a square box is: is the mass scaling function.

[0091] In this embodiment, the mass scaling function satisfies the following relationship: in, is the mass scaling function, is the side length of the square box, is the multifractal order partition function, is the order of the statistical moment.

[0092] Furthermore, in this embodiment, the multifractal spectrum satisfies the following relationship: in, is the multifractal spectrum, is the singular index, is the order of the statistical moment, is the mass scaling function.

[0093] S43. Obtain microstructural characteristic analysis results of the limestone test sample based on the analysis of the microstructural characterization results.

[0094] For details, see Fig.13 , the figure shows the multi-fractal spectrum of the limestone test sample, according to Fig.13 As shown in Figure 2, with the increase of dynamic dissolution cycle, the multifractal spectrum of the limestone test sample gradually moves to the high The movement of the zones indicates that the pore characteristics of the limestone test samples are gradually becoming more obvious.

[0095] In this embodiment, using and To describe the multi-fractal characteristics of the pores of the limestone test sample, Used to describe the pore distribution characteristics of limestone test samples, The smaller it is, the smaller the pore distribution area is and the more uniform its distribution is; Reflects the global expansion of the pores in the limestone test sample, The larger the size, the higher the degree of pore development and expansion.

[0096] Specifically, the and , satisfying the following relationship: in, is the change value of the singular index, is the singular index when the maximum probability subset reflects the most pores, is the singular index when the minimum probability subset reflects the least porosity, is the variation value of the multifractal spectrum, is the number of boxes that reflects the fractal subset with the maximum probability, is the number of boxes that reflect the fractal subset with the minimum probability.

[0097] For more details, see Fig.14 The figure shows the variation curve of multiple fractal characteristic parameters of limestone test samples. Fig.14 As shown in Figure 2, with the increase of dynamic dissolution cycle, the From 1.03 to 1.77, The increase from 1.35 to 1.85 indicates that the pore structure of the rock matrix of the limestone test sample gradually develops, the internal fragmentation of the limestone test sample intensifies, and the microstructural stability of the limestone test sample decreases.

[0098] S5. Analyze the degradation mechanism of the mechanical properties of limestone by combining the test results and the microscopic characteristic analysis results.

[0099] Among them, S5 specifically includes the following steps: S51. Constructing the relationship between the microstructural degradation characteristics and the uniaxial compressive strength of the limestone test sample based on the microstructural characteristic analysis results.

[0100] For details, see Fig.15 The figure shows the multi-fractal characteristic parameters and the degradation rate of the uniaxial compressive strength of the limestone test sample. Fig.15 As shown, and There is a good linear relationship between them and the degradation rate of the uniaxial compressive strength stage, indicating that the multi-fractal characteristic parameters of pores can characterize the changes in the macroscopic mechanical properties of limestone test samples.

[0101] in, Fig.15 Medium R 2 Used to measure the fitting effect of the fitting curve, R 2 The value range is [0,1], R 2 The closer the value is to 1, the better the fitting effect is.

[0102] S52. Analyze the degradation mechanism of the mechanical properties of limestone based on the changing relationship between the microstructural degradation characteristics and the uniaxial compressive strength.

[0103] in accordance with Fig.15 As shown, and They are positively correlated with the degradation rate of the uniaxial compressive strength stage, indicating that the continuous dynamic dissolution will cause some mineral particles to absorb water and expand and lose water to shrink, resulting in cracks or fissures between the originally tight mineral particles, allowing the solution to further penetrate into the internal area of ​​the rock mass. The lubrication of the solution will cause the connection and friction between the mineral particles to decrease, and the pore water pressure caused by the invasion of the aqueous solution will promote the development and expansion of defective areas such as internal cracks and pores. At the same time, the solution invading the rock mass will react chemically with some mineral particles, thereby forming dissolution pores and gradually developing, and even destroying the stability of the internal structure of the sample, ultimately causing a significant degradation of the macroscopic mechanical properties of the sample.

[0104] See also Fig.16 In an optional embodiment, in order to efficiently execute the method for analyzing the mechanical properties degradation mechanism of limestone in karst areas provided by the present invention, the present invention provides a system for analyzing the mechanical properties degradation mechanism of limestone in karst areas, the system comprising an input device, an output device, a processor and a memory, the hardware facilities being interconnected, wherein the memory is used to store a computer program, the computer program comprising program instructions, the processor being configured to call the program instructions and execute the specific steps of the relevant embodiments of the method for analyzing the mechanical properties degradation mechanism of limestone in karst areas provided by the present invention. The system for analyzing the mechanical properties degradation mechanism of limestone in karst areas provided by the present invention has a complete structure, is objective and stable, and can efficiently execute the method for analyzing the mechanical properties degradation mechanism of limestone in karst areas provided by the present invention, thereby improving the overall applicability and practical application capability of the present invention.

[0105] In summary, the method of the present invention provides a method and system for analyzing the degradation mechanism of the mechanical properties of limestone in karst areas; the present invention constructs a dynamic dissolution test in a CO2 solution environment by means of gas-liquid circulation, which can more realistically and effectively analyze the degradation process of limestone in karst areas, and analyzes the degradation law of the mechanical property parameters of limestone in karst areas based on the dynamic dissolution test. The method of the present invention is easy to understand, simple to calculate, and has a small workload, which is conducive to engineering applications and provides a theoretical basis and technical support for the further development of the field of rock analysis technology.

[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas, characterized in that: The steps include: Obtain limestone test samples from limestone formations in karst areas; Based on testing the limestone test sample to obtain test results; Observing the limestone test sample to obtain microscopic characteristic observation results of the limestone test sample; Obtaining microscopic characteristic analysis results of the limestone test sample based on analysis of the microscopic characteristic observation results; The degradation mechanism of the mechanical properties of limestone is analyzed by combining the test results with the microscopic characteristic analysis results.

2. The method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas according to claim 1 is characterized in that: The step of obtaining limestone in the karst area and constructing a limestone test sample comprises: A cylindrical limestone sample is obtained by pre-treating the limestone in the karst area; Obtaining a limestone characteristic sample based on the cylindrical limestone sample; A limestone test sample is obtained based on the limestone characteristic sample.

3. The method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas according to claim 2 is characterized in that: The test results obtained based on the test of the limestone test sample include: Obtaining a stress-strain variation relationship of the limestone test sample based on the test; Obtaining the energy variation relationship of the limestone test sample according to the test; Constructing a tensile strength variation relationship of the limestone test sample according to the test; The test is used to obtain the shear stress-shear displacement variation relationship of the limestone test sample.

4. The method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas according to claim 3 is characterized in that: The energy change relationship of the limestone test sample obtained according to the test includes: in, is the total energy of the limestone test sample, is the stress of the limestone test sample, is the strain of the limestone test sample.

5. The method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas according to claim 3 is characterized in that: The step of observing the limestone test sample to obtain the microscopic characteristic observation results of the limestone test sample includes: Obtaining microscopic morphological characteristics of the limestone test sample based on scanning observation of the limestone test sample; The microstructural characteristics of the limestone test sample are obtained based on scanning observations of the limestone test sample.

6. The method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas according to claim 5 is characterized in that: The microscopic characteristic analysis results of the limestone test sample obtained based on the analysis of the microscopic characteristic observation results include: Preprocessing the microstructure characteristics to obtain a microstructure characteristic image of the limestone test sample; Characterizing the microstructural features based on the microscopic feature image to obtain a microstructural characterization result of the limestone test sample; The microstructural characteristic analysis results of the limestone test sample are obtained based on the analysis of the microstructural characterization results.

7. The method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas according to claim 6 is characterized in that: The characterizing the microstructure of the limestone test sample based on the microscopic characteristic image to obtain a microstructure characterization result includes: in, Multifractal The partition function of order, is the order of the statistical moment, is the side length of the square box, Count the total number of square boxes, is the traversal count, For the The probability distribution of pixels in a square box is: is the mass scaling function.

8. The method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas according to claim 7 is characterized in that: The mass scaling function comprises: in, is the mass scaling function, is the side length of the square box, is the multifractal order partition function, is the order of the statistical moment.

9. The method for analyzing the degradation mechanism of mechanical properties of limestone in karst areas according to claim 6, characterized in that: The analysis of the degradation mechanism of the mechanical properties of limestone by combining the test results with the microscopic characteristic analysis results includes: Based on the microstructural characteristic analysis results, a variation relationship between the microstructural degradation characteristics and the uniaxial compressive strength of the limestone test sample is established; The degradation mechanism of the mechanical properties of limestone is analyzed based on the changing relationship between the microstructural degradation characteristics and the uniaxial compressive strength.

10. A system for analyzing the degradation mechanism of mechanical properties of limestone in karst areas, characterized in that: The system includes an input device, an output device, a processor and a memory, wherein the input device, the output device, the processor and the memory are interconnected, wherein the memory is used to store a computer program, the computer program includes program instructions, and the processor is configured to call the program instructions to execute the method for analyzing the degradation mechanism of the mechanical properties of limestone in karst areas as described in any one of claims 1 to 9.

Citation Information

Cited By

  • Layered rock mass numerical simulation method based on mixed progressive failure model

    CN120688214A